Health ecology : health, culture, and human-environment interaction - Hunarī, Murtaz̤á; Boleyn, Thomas, 1952- (Routledge, 1999)
This ground-breaking study offers new challenges to those teaching, studying or developing strategies and policies in health and the environment. Bringing together a variety of approaches from different perspectives and different locations, the contributors examine the various dimensions of health ecology in a human ecology framework, examining how local, regional and global factors impinge upon the health and environment of individuals, communities and the globe.